Pengaruh Promosi & Rating Produk Terhadap Loyalitas Pelanggan Yang Dimediasi Olehcustomer Satisfaction Pada Konsumen Roughneck E-Commerce Tokopedia (Studi Pada Mahasiswa Di Kota Malang) - Haidi, Mukhammad Maulana; Malikah, Anik; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study was conducted to determine the influence of product promotion and rating on customer loyalty mediated by customer satisfaction on roughneck e-commerce consumers at Tokopedia (a study of students in Malang City). This study uses a quantitative approach with an explanatory research type. The research population is students in Malang who shop for Roughneck brand products on the e-commerce site Tokopedia, with a sample of 80 respondents selected using a non-probability sampling technique with a purposive sampling approach. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS 4.0 software. The results of this study indicate that promotions have an influence on customer loyalty, product ratings do not have an influence on customer loyalty, promotions have an influence on customer satisfaction, ratings have an influence on customer satisfaction, customer satisfaction does not have an influence on customer loyalty, promotions do not have an influence on customer loyalty through customer satisfaction, and product ratings do not have an influence on customer loyalty through customer satisfaction. Keywords: promotions, product ratings, customer loyalty, customer satisfaction